2005
DOI: 10.1002/jrs.1263
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational study and lattice dynamics of disordered NaBi(WO4)2

Abstract: Polarized Raman and IR spectra were obtained for NaBi(WO 4 ) 2 crystal at ambient temperature. Assignment of the observed bands to the respective internal and external phonons was proposed on the basis of lattice dynamics calculations. The spectra showed also the appearance of additional Raman and IR bands which are not predicted from group theory for the scheelite I4 1 /a structure. It is argued that these bands result from symmetry breakdown induced by cation disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…For the pure (Li 0.5 Bi 0.5 )MoO 4 , more Raman active modes (weak and overlapping) are observed than that of BiVO 4 . The strongest modes at around 872.3 cm À1 are assigned to v s (MoO 4 ), and the weak modes near 772.4 cm À1 are assigned to v as (MoO 4 ) [31][32][33][34][35]. The v s (MoO 4 )-related modes can be observed in samples with very little substitution of Mo for V on the B-site (even as low as x = 0.03), and the Raman spectra give much more detailed information for the local structure than the XRD results reported in our previous work [17].…”
Section: Resultsmentioning
confidence: 99%
“…For the pure (Li 0.5 Bi 0.5 )MoO 4 , more Raman active modes (weak and overlapping) are observed than that of BiVO 4 . The strongest modes at around 872.3 cm À1 are assigned to v s (MoO 4 ), and the weak modes near 772.4 cm À1 are assigned to v as (MoO 4 ) [31][32][33][34][35]. The v s (MoO 4 )-related modes can be observed in samples with very little substitution of Mo for V on the B-site (even as low as x = 0.03), and the Raman spectra give much more detailed information for the local structure than the XRD results reported in our previous work [17].…”
Section: Resultsmentioning
confidence: 99%
“…From our most recent examination of NaBi(WO 4 ) 2 , however, it is clear that the exact crystal symmetry is I4 1 =a [14] and the previously observed symmetry lowering possibly is due to non-stoichiometry. Small anomaly arriving at about 241 K in the dielectric permittivity measured as a function of temperature was interpreted as a structural phase transition [15].…”
Section: Introductionmentioning
confidence: 85%
“…A vibrational and EPR spectroscopic investigation of heavy-metaloxide glasses and vitro-ceramics containing manganese, 252 and a temperature-dependent Raman spectroscopic study of K 0.2 Na 0.8 NbO 3 ceramics 253 were subjects of other studies. Finally, Maczka et al 254 reported the lattice dynamics of disordered NaBi WO 4 2 and argued that the additionally observed Raman bands were due to symmetry breakdown induced by cation disorder.…”
Section: Glasses Ceramics Disordered Materialsmentioning
confidence: 99%